Taxonomia e distribuição geográfica de Notonectidae (Hemiptera: Nepomorpha) nos estados do Amazonas, Pará, Rondônia e Roraima, Brasil - Barbosa, Julianna Freires (Instituto Nacional de Pesquisas da Amazônia - INPA, 2010)
Until this study, 24 species of Notonectidae, from the genera Martarega White, 1879, Notonecta Linnaeus, 1758 and Buenoa Kirkaldy, 1904 had records restricted mainly to the states of Amazonas and Pará in political Northern Brazil. The area of this study comprised 44 municipalities in the states of Roraima, Amazonas, Pará and Rondônia. This work raised to 33 the number of known species in the region: 21 known species were found, 7 species recorded through literature, 3 new species of Martarega and 2 of Buenoa have been described. Martarega brasiliensis Truxal, 1949 and B. salutis Kirkaldy, 1904 constitutes the first records in the State of Roraima. Buenoa platycnemis (Fieber), 1851, B. femoralis (Fieber), 1851 and B. unguis Truxal, 1953 constitutes new records in the state of Amazonas. Martarega uruguayensis (Berg), 1883, N. disturbata Hungerford, 1926, B. tibialis Truxal, 1957, B. amnigenoidea Nieser, 1970 and B. truxali Nieser, 1968 constitutes new records in the State of Pará, and B. macrotrichia Truxal, 1953 constitutes the first record in Brazil in this state. Martarega uruguayensis and M. gonostyla Truxal, 1949 are new records in the State of Rondônia, and B. truxali constitutes the first record of Buenoa in this state. Keys are provided for identification of species that occur in the region, coupled with elucidating illustrations. The distribution of species was revised due to numerous political changes and errors related to label information.
Keywords: Heteroptera; Martarega; Insetos aquáticos